Pengaruh Kualitas Pelayanan dan Lingkungan Kerja Terhadap Kepuasan Pelanggan Kapal Mutiara Berkah 1 - M. Ferlin Aziz Hakim; Ardansyah; Hepiana Patmarina (Jurnal EMT KITA, 2023)
This study aims to determine the effect of differences (independent variable) on what (dependent variable). The higher the quality of service provided by PT Pelabuhan Indonesia (Persero) Regional 2 Panjang, the more satisfied the customers will be. The work environment can also affect customer satisfaction, so it is important to ensure that the conditions in the port work environment are good. The sample uses 100% of the population. Multiple linear regression analysis is a way to analyze data using the method, testing this hypothesis refers to testing (t) and testing (f). The results of this study indicate that good service makes the customers of the Mutiara Berkah 1 ship happy, and a good working environment makes the customers of the Mutiara Berkah 1 ship feel happy.